Catalytic cascade reactions - Xu, Peng-Fei, 1964-; Wang, Wei (Associate professor of chemistry) (Hoboken, New Jersey : Wiley, 2013)
'The development of catalytic versions of cascade reactions has become one of the most active and burgeoning reaction areas in organic synthesis. Covering both organocatalysis and transition-metal catalysis for these reactions, Catalytic Cascade Reactions illustrates the versatility and application of cascade reactions for synthesizing valuable compounds, such as drugs and natural products. Highlighting catalytic versus non-catalytic reactions, an important shift in academic and industry practice, the text brings chemists and the organic synthesis community up to speed on the many recent advances in the field'--
'This book covers recent and important discoveries and activities in catalytic cascade reactions, an emerging and dynamic direction for organic synthesis'--
Includes bibliographical references and index.
Keywords: Organic reaction mechanisms; Catalysis; Chemical reactions; Organic compounds -- Synthesis